Central auditory masking by an illusory tone. - Christopher J Plack; Andrew J Oxenham; Heather A Kreft; Robert P Carlyon (PLoS ONE)
Many natural sounds fluctuate over time. The detectability of sounds in a sequence can be reduced by prior stimulation in a process known as forward masking. Forward masking is thought to reflect neural adaptation or neural persistence in the auditory nervous system, but it has been unclear where in the auditory pathway this processing occurs. To address this issue, the present study used a "Huggins pitch" stimulus, the perceptual effects of which depend on central auditory processing. Huggins pitch is an illusory tonal sensation produced when the same noise is presented to the two ears except for a narrow frequency band that is different (decorrelated) between the ears. The pitch sensation depends on the combination of the inputs to the two ears, a process that first occurs at the level of the superior olivary complex in the brainstem. Here it is shown that a Huggins pitch stimulus produces more forward masking in the frequency region of the decorrelation than a noise stimulus identical to the Huggins-pitch stimulus except with perfect correlation between the ears. This stimulus has a peripheral neural representation that is identical to that of the Huggins-pitch stimulus. The results show that processing in, or central to, the superior olivary complex can contribute to forward masking in human listeners.